(untitled) (Update Dental College Journal, 2019)
Background: Children with disabilities and special needs present unique challenges for oral health professionals in the planning and carrying out of dental treatment. oral health care workers need to take cognizance of when preparing treatment plans for children with special needs. Children with disabilities are considered to be a high risk group for dental diseases specially dental caries and periodontal disease. High rates of dental caries, missing teeth, periodontal disease and malocclusion are all indicators of poor oral health of children with disabilities. Objectives:The aim of the study was to assess the oral health status of disabled children in special schools of Dhaka city. Study design: This was a cross sectional study. Study settings and period: The study was conducted in two elementary schools at mirpur area of Dhaka city in the period between of between february 2014 to January 2015. Subjects: 200 disabled children with the age range from 6 to 14 belonging to six different disability groups were examined. Participants were grouped according to their type of disability autistic children, Down syndrome, Cerebralpulsy, mute and deaf, blind and physical disability. Methods: Data was collected by using semi structured quationnaire and checklist.Datawere analyzed by statistical package of social science(SPSS- 20). Results: According to disability the participants autistic 44%, cerebral pulsy 37%, down syndrome 35%, blind 28%, deaf and mute 30% and physical disability 30%.The average number of decayed tooth was found 6.89%. Mean DMFT value was 4.75. Average number of missing tooth was 1.89%.Prevalence of dental caries highest 71% in autistic children then other cetagory of disabilty .Oral hygiene practice of the respondent found very poor.76% children brush teeth in the morning and once in a day.49% respondent use toothpick to clean food from in between teeth.37% of the respondent never visited to dentist. 34.5% respondents had normal gingiva, 49% had mild gingivitis and 16.5% had marked gingivitis. Highest numbers of trauma cases were recorded in visually impaired group. 98.7% children required some form of dental treatment. Conclusion: Oral health status of children with disabilities was poor and it is important to concentrate on a preventive approach and provide proper dental education to parents of disabled childrens. More attention should be paid to the oral hygiene practice of disabled children Update Dent. Coll. j: 2019; 9 (2): 32-35